PENGARUH PRICES DISCOUNT DAN STORE ADMOSPHERE TERHADAP LOYALITAS PELANGGAN GUNA MENINGKATKAN KEPUTUSAN PEBELIAN PADA MINIMARKET HYPERMART LIPPO DI LUBUK LINGGAU - Adi Sismanto; Wulandari Wulandari (Jurnal Entrepreneur dan Manajemen Sains (JEMS), 2023)
This study aimed to determine the effect of price discount and store atmosphere on customers’ loyalty to increase purchasing decision at Hypermart Lippo in Lubuk Linggau. This study used total sampling based on predetermined criteria with totaling 157 respondents. The data collection techniques used observation, documentation and questionnaire. The results showed that The price discount (Xl) has an effect on customers’ loyalty (Y) in using products with a path coefficient of I.306. The store admosphere (X2) has effect on customers’ loyalty (Y) in using products by 1.109. The customers’ loyalty (Y) has effect on purchasing decision (YI) in using the product with a coefficient of 0.410. The price discount (Xl) has an indirect effect on purchasing decision (Z) in using the product with a coefficient of 0.870. The store atmosphere (X2) has an indirect effect on purchasing decision (Z) in using products with a coefficient of 0.468. The customers’ loyalty (Y) has effect on consumers’ purchasing decision (Y1) of daily necessities products in Lubuk Linggau with a coefficient ß of 0.371 or 37.1% and there is a positive and significant effect on price discount on consumers’ purchasing decision. Keywords: Price Discount, Store Atmosphere, Customer Loyalty. Purchasing Decision.